A new record for the Flora of Turkey: Sempervivum marmoreum (Crassulaceae) - Sabdani, Mardiya; Haşayacak, Hasan; Bani, Barış (Biological Diversity and Conservation, 2025)
Abstract This study deals with a species belonging to the genus Sempervivum which has not yet been recorded in the Flora of Turkey. The morphological characters of the species were investigated, and a distribution map was also presented. For its morphological treatment, a detailed description of the species is given. A thorough morphological examination was conducted to confirm the identification of the newly recorded species, emphasizing the unique traits that separate it from the other Sempervivum taxa. Therewith, the collected plant specimens were identified as Sempervivum marmoreum subsp. reginae-amaliae. Notably, S. marmoreum is known for its occurrence and adaptability across various European habitats, but it is a new record for Türkiye.